소포자 배양으로 육성된 구가 크고 곧은 배추 계통 ‘원교20038호’ - 장하영(Ha-Young Jang); 박민영(Min Young Park); 장석우(Suck-Woo Jang); 윤무경(Moo-Kyoung Yoon); 이정수(Jung-Soo Lee); 박수형(Suhyoung Park) (Korean journal of breeding, 2017)
Kimchi cabbage (known as Chinese cabbage) is major vegetable in Korea. An inbred line of ‘Wonkyo20038ho’, was developed by the National Institute of Horticultural & Herbal Science, RDA in Republic of Korea. The microspore culture was carried out using ‘Chunhuigohangwang’ which was introduced from China in 2002. Among 3 DH inbred lines, ‘Wonkyo20038ho’ inbred line was finally selected after field exhibition in 2009. The horticultural traits of ‘Wonkyo20038ho’ inbred line; half-open head, white inner leaf colour, and dark green outer leaf colour. The average (for four years) head weight was 2025.3g, and head width and height were 15.8cm and 32.4cm, respectively. Head shape was narrow elliptic and degree of overlapping leaf was medium. Numbers of outer and internal leaves were 14.1 and 49.8, respectively. Harvest maturity was mid-late maturing type and average of seed yield for five years was 926 seeds. In addition, ‘Wonkyo20038ho’ inbred line is suitable for salad in that it possessed few trichome and narrow elliptic head shape.